Reliability analysis and reliable operation of three-level ANPC inverter - Zheng, Xiaolin; Huang, Xiaoxiao; Chen, Peiyu; Chong, Zhiqiang; Yuan, Zhongchen (Frontiers in Energy Research, 2023)
The three-level active neutral-point-clamped (3L-ANPC) inverters have been widely used in medium-voltage high-power electrical drives. The purpose of this paper is to achieve the reliable operation for 3L-ANPC inverters by reliability analysis and optimal switching and control strategies, while the performance of output waveforms of inverters is maintained. This paper starts by analyzing the power loss and the reliability of power semiconductor devices. On this basis, a mathematical model is derived for online condition monitoring of semiconductor devices. Then, the modulation strategies of the passive commutation mode and the active commutation mode are designed for the 3L-ANPC inverter, and the power loss distributions are analyzed among different semiconductor devices accordingly. Finally, three optimized strategies are designed to improve the reliability of the 3L-ANPC inverter under different load conditions based on different commutation modes and the developed reliability model. Both the simulation using MATLAB Simulink as well as PLECS have been conducted to verify the validity of analysis and control for improving reliability of 3L-ANPC inverters in this paper.